Apuntes en torno a las prácticas antisindicales: ¿Es realmente posible probarlas? - Vilchez Garcés, Lidia (2017)
In this article, one of the most important labor law institutions is reviewed, as it is freedom of association and, in return, the clearest statement of its violation: anti-union behavior. The issue highlights complexity, in so far as this type of proscribed behaviors can be realize in different and subtle ways, being of special interest to address the interference of the employer in the administration of the labor union, as well as the difficulties involved in its evidence.